1999
DOI: 10.1038/sj.ejhg.5200257
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally observed germline mutations at human micro- and minisatellite loci

Abstract: We have analysed close to 30 000 human germline transmission events at five microsatellite loci (D3S1359, HumTH01, HumvWA, HumTPO and HumFES) and four minisatellite loci (D1S80, ApoB, Col2A1 and D17S30). At these loci the mutation rates are similar at the microsatellite and the minisatellite loci, varying from 0.2 ؋ 10 -3 to < 3.3 ؋ 10 -3 and from 0.5 ؋ 10 -3 to 1.5 ؋ 10 -3 , respectively. Interestingly, paternal mutations appeared to be dominant at the microsatellite loci, whilst maternal mutations are domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 25 publications
5
36
1
1
Order By: Relevance
“…On a per-generation basis, the mutation rates that we report for C. elegans and D. pulex are much lower than those previously estimated for humans (Heyer et al 1997;Brinkmann et al 1998;Sajantila et al 1999;Kayser et al 2000;Leopoldino and Pena 2003;Dupuy et al 2004;Ballard et al 2005;Gusmao et al 2005;Henke and Henke 2006;Yan et al 2006;Hohoff et al 2007;Lee et al 2007), but much higher than those for yeast (Henderson and Petes 1992;Strand et al 1993;Johnson et al 1996;Sia et al 1997Sia et al , 2001Wierdl et al 1997;Hawk et al 2005;Legendre et al 2007). In principle, such differences could simply arise as a consequence of the pronounced variation in the numbers of germline cell divisions per generation that exists among these species (1, 10, and $200, respectively, in Saccharomyces cerevisiae, C. elegans, and Homo sapiens; Kimble and Ward 1998;Crow 2000).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…On a per-generation basis, the mutation rates that we report for C. elegans and D. pulex are much lower than those previously estimated for humans (Heyer et al 1997;Brinkmann et al 1998;Sajantila et al 1999;Kayser et al 2000;Leopoldino and Pena 2003;Dupuy et al 2004;Ballard et al 2005;Gusmao et al 2005;Henke and Henke 2006;Yan et al 2006;Hohoff et al 2007;Lee et al 2007), but much higher than those for yeast (Henderson and Petes 1992;Strand et al 1993;Johnson et al 1996;Sia et al 1997Sia et al , 2001Wierdl et al 1997;Hawk et al 2005;Legendre et al 2007). In principle, such differences could simply arise as a consequence of the pronounced variation in the numbers of germline cell divisions per generation that exists among these species (1, 10, and $200, respectively, in Saccharomyces cerevisiae, C. elegans, and Homo sapiens; Kimble and Ward 1998;Crow 2000).…”
Section: Discussionmentioning
confidence: 42%
“…Such slippage adds or deletes repeat units from the newly synthesized strand at a frequency that depends on factors such as overall length, repeat type, flanking sequence, and recombination rate (Schlötterer 2000). Previous estimates of microsatellite mutation rates in animals ½direct estimates derived from individuals with known parentage (Brinkmann et al 1998;Sajantila et al 1999;Leopoldino and Pena 2003;Henke and Henke 2006;Hohoff et al 2007) and indirect estimates based on the application of models of microsatellite evolution to standing patterns of variation (Chakraborty et al 1997) are as high as 10 À3 and 10 À4 / locus/generation. Most studies show that the spectrum of microsatellite mutations is heavily dependent on allele size (Xu et al 2000;Lai and Sun 2003) and suggest that the mechanism may be more complex than the simple stepwise mutation model (Brohede et al 2002;Huang et al 2002;Calabrese and Durrett 2003).…”
mentioning
confidence: 99%
“…Normally, when the generation of errors and their repair are in balance, the mutation frequency at STRs has been estimated to be roughly one mutation per one thousand cell divisions (Weber & Wong, 1993). Family studies of STR markers have revealed a germline mutation rate from 10 − 4 to 10 − 2 , correlating with structural parameters such as the number and complexity of the repeats (Brinkmann et al 1998a(Brinkmann et al , 1998bSajantila et al 1999;Kayser et al 2000;Kayser & Sajantila 2001;Leopoldino & Pena 2003).…”
Section: Population Datamentioning
confidence: 99%
“…However, despite intense study, many aspects of microsatellite evolution remain unresolved. For example, although most mutations involve the gain or loss of a single repeat unit, some studies report a tendency for gains in length to outnumber losses Kayser et al 2000;Dupuy et al 2004), while others report either unbiased mutations (Brinkmann et al 1998;Xu et al 2000) or a tendency to decline in length (Sajantila et al 1999) especially among very long microsatellites (Xu et al 2000;Huang et al 2002). Mutation rates and other properties appear to depend critically on the structure of the microsatellite, with repeat number and the degree of interruption both being important (Brinkmann et al 1998;Kayser et al 2000Kayser et al , 2004Huang et al 2002).…”
mentioning
confidence: 99%